Australian Rural Identities in Barbara Baynton’s Bush Studies - Donny Syofyan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2021)
Barbara Baynton, in her collection of short stories, Bush Studies, examines the various types of people that exist in the rural regions of Australia. She presents a study of different identities that were left out or wrongly represented in the traditional narratives of Australian national identity at the time. She dismantled the widespread and broadly accepted bush narrative of the Australian national identity that played a significant role in the marginalization of anyone who was not White and Male. Qualitative method is used to determine the accuracy of the hypothesis. It was observed that the women and people of other ethnicities belonging to the rural Australian region were marginalized through wrongful representation or no representation in the narrative of national identity and Barbara Baynton makes efforts in Bush Studies to do otherwise. She depicts the sufferings and psyche of the people in the rural region and presents a new layer of their identities. The theory used is Postcolonial Criticism.